PENCATATAN KELAHIRAN MELEWATI BATAS WAKTU PRA DAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XI/2013 (STUDI KASUS DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA MEDAN) - BERTY TARIGAN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. BUDIMAN GINTING 2. SUNARMI3. T. KEIZERINA DEVI A Basically, each birth should be reported to the related Agency at least 60 (sixty) days since the birth and the registration which exceeds 1 (one) year deadline should be carried out according to the Court's Verdict as stipukated in Article 32, paragraphs 1, 2, and 3 of Law No. 23/2006 on Aminduk (Population Administration). There is a problem in Article 32 of Law on Aminduk so that it has to be judicial reviewed, and now it is considered legally invalid.The objective of the research is to find out 1) the implementation of makinng birth certificates according to Law No. 23/2006 on Aminduk and the Constitutional Court's Ruling No. 18/PUU-XI/2013 at the Dukcapil (Civil Registry and Population) Office of Medan, 2) the consequence of the Constitutional Court's Ruling No. 18/PUU-2013 on protoviding birth certificates which exceed the deadline in the pre and post the Constitutional Court's Ruling No. 18/PUU-XI/2013 at the Dukcapil Office of Medan, and 3) the obstacles faced by the Dukcapil Office of Medan in providing certificates which exceed the deadline in the post Constitutonal Court's Ruling No. 18/PUU/XI/2013 and the efforts to handle the obstacles. The research used field research method in which primary data were obtained directly from the employees of the Dukcapil Office in providing childbirth certificates.Keywords: Birth Registration, Deadline, Pre and Post, Constitutional Court's Ruling